Exceptionally thermally conductive and electrical insulating multilaminar aligned silicone rubber flexible composites with highly oriented and dispersed filler network by mechanical shearing. (May 2021) - Xue, Yang; Wang, Haosheng; Li, Xiaofei; Chen, Yunfa
Graphical abstract: Highlights: Constructing multilaminar aligned SABE flexible composites. BN and EG with high orientation and dispersion forming thermally conductive network up to 23.4 W m −1 K −1 . Enhanced thermal conductivity and maintained electrical insulate properties. Abstract: The design of multilayered structure network is an effective strategy to enhance the thermal conductivity and maintain the electrical insulating performance of thermal management materials. Multilaminar aligned silicone rubber (SR) flexible hybrids (SABE) with highly oriented and dispersed boron nitride (BN) and expanded graphite (EG) filler network were constructed successfully through layer by layer assembly of SR/ABN and SR/AEG prefabricated by a facile and scalable strategy of mechanical shearing. The SABE-6 composite with 4 assembly circles exhibited excellent in-plane thermal conductivity (TC) of 23.4 W m −1 K −1 and outstanding electrical insulation (volume resistance > 10 14 Ω∙cm), which displayed the highest value among reported thermal conductive SR-based composites. The TC of SABE composite showed 14379% and 178% higher than that of pure SR and simple blending SR/BN/EG (SBE) composites, respectively, which ascribed to the highly oriented and dispersed filler network. The study provides a high property of SR-based composite thermal management materials.